Analisis Pengaruh Variasi Parameter Mesin CNC Lasser Cuting terhadap Hasil Pemotongan Material SPHC 5 mm di PT. XYZ - Mochammad Rajib El Atros; Hadi Nurwahyudin; Mohadly Satya Permadi (Proklamasi 45 University, 2025)
This study analyzes the effect of parameter variations on CNC Laser Cutting machines on the cutting quality of 5 mm SPHC material at PT. XYZ. The tested parameters include cutting speed, laser power, gas pressure, and the type of gas used. The research methods involve literature review, observation, and experiments with variations in cutting parameters. The results show that the proper combination of parameters significantly affects cutting quality, including edge cleanliness, oxidation levels, and surface quality. The use of high-pressure nitrogen produces cleaner and neater cuts compared to oxygen, which tends to cause oxidation. Additionally, cutting speed and laser focus position also have a significant impact on the final results. This study emphasizes that optimizing parameters in CNC Laser Cutting machines can improve efficiency and precision in the SPHC material cutting process, leading to better results in the manufacturing industry.